Tomographic analysis of the apical anatomy of mandibular first and second premolars in central India population - Ruchi Verma; Suparna Ganguly Saha; Arati Chaudhary; Anuj Bharadwaj; Shrija Paradkar; Sheetal Khandelwal (Wolters Kluwer Medknow Publications, 2021)
Aim: Aim of the present study was to evaluate the distance of the apical foramen in relation to the anatomical apex of mandibular premolars by Cone Beam Computed Tomography (CBCT) in a selected population of Central India. Objectives: To evaluate and compare the distance between the apical foramen and the anatomic apex of the mandibular first and second premolars of both the sides of mandible and in both the genders in a selected population of Central India. Material and Methods: In this cross-sectional study, screening of total 250 CBCT scans of patients with a minimum age of 20 years, were evaluated and only 170 CBCT images (88 males and 82 females) were considered for the study based on the inclusion criteria. Furthermore, scans were observed in axial, sagittal and coronal planes. Results: Average (±SD) distance from apical foramen to the anatomic apex of first and second premolars in male was 0.61 - 0.62 mm and for females was 0.58 - 0.60 mm. No statistical significant difference was found between right and left quadrant and in males and females. Conclusion: The study demonstrated that minimum 1mm of distance from the anatomic apex in mandibular premolars could be appropriate for root canal therapy.